Between Central and Peripheral: The Views of amina wadud and Faqihuddin Abdul Kodir on Islamic Feminism - Muhammad Syāmil Basāyif (UIN Sunan Kalijaga Yogyakarta, 2025)
This article discusses two feminist thinkers, amina wadud and Faqihuddin Abdul Kodir, who articulate similar ideas of Islamic feminism through different approaches. wadud represents thinkers who live in the ‘central’ environment of feminist discourse, while Faqih indicates how ‘peripheral’ currents creatively adopt and adapt such discourse. This article argues that differences in intellectual formation and socio-cultural background strongly shape how each engages the Qurʾān, which in turn affects their respective attitudes toward classical traditions, particularly tafsir and uṣūl al-fiqh. This article discusses how their hermeneutical frameworks interpret Qur’anic gender verses, where their similarities and differences lie in their approaches to tafsir, both in terms of methodology and exegetical outcomes, and especially how they resist, receive, and reconfigure the classical tradition. Ultimately, this study shows that wadud, situated within the ‘central’ domain of feminist theory and influenced by secular-liberal paradigms, tends toward a deconstructive posture that challenges classical traditions. In contrast, Faqih, who was educated in traditional academia and lives in a ‘peripheral’ context, while inspired and influenced by wadud, adapts feminist ideas in ways that are more appreciative of the classical intellectual heritage.Abstrak Artikel ini membahas dua pemikir feminis, Amina Wadud dan Faqihuddin Abdul Kodir, yang mengartikulasikan gagasan feminisme Islam yang serupa melalui pendekatan yang berbeda. Wadud merepresentasikan pemikir yang beroperasi dalam lingkungan ‘sentral’ diskursus feminis, sementara Faqih menunjukkan bagaimana arus ‘perifer’ secara kreatif mengadopsi dan mengadaptasi diskursus tersebut. Artikel ini berargumen bahwa perbedaan latar belakang intelektual dan konteks sosio-kultural secara signifikan membentuk cara masing-masing tokoh berinteraksi dengan Al-Qur’an, yang pada gilirannya memengaruhi sikap mereka terhadap tradisi klasik, khususnya tafsir dan uṣūl al-fiqh. Pembahasan difokuskan pada bagaimana kerangka hermeneutik keduanya menafsirkan ayat-ayat Al-Qur’an tentang gender, dengan menyoroti persamaan dan perbedaan dalam pendekatan tafsir, baik dari segi metodologi maupun hasil penafsiran, serta cara mereka merespons, menerima, dan merekonfigurasi tradisi klasik. Pada akhirnya, studi ini menunjukkan bahwa Wadud, yang berada dalam ranah sentral teori feminis dan dipengaruhi oleh paradigma sekuler-liberal, cenderung mengambil sikap dekonstruktif yang menantang tradisi klasik. Sebaliknya, Faqih, yang ditempa dalam tradisi akademik keislaman dan hidup dalam konteks perifer, meskipun terinspirasi dan dipengaruhi oleh Wadud, mengadaptasi gagasan feminis dengan cara yang lebih apresiatif terhadap warisan intelektual klasik.